Sistem Informasi Rekam Medis Paru berbasis Web (Studi Kasus : Rumah Sakit Karsa Husada Batu) - Rizki Aziz Amanullah; Achmad Arwan; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Lung Medical Record Information System is a system intended to assist doctors and nurses in managing lung patient data along with storing medical record data of patients who have visited. In examining patients, doctors and nurses conduct initial assessments which include initial nursing assessments, and patient medical assessments. The patient's medical assessment includes anamnese, physical examination, supporting investigation, diagnosis, follow-up, and progress notes. The follow-up section, the patient will be outpatient or inpatient and will be treated. Inpatient medical records consists of inpatient identity, anamnese, physical examination, list of problems, and chest radiographs. The development of the pulmonary medical record system took a case study at the Karsa Husada Batu Hospital. The system development process starts from the requirements analysis to the testing section with an object oriented approach. At requirement analysis stage there are 111 functional requirements. The system implementation phase is carried out using the Laravel framework. Unit testing produce 100% valid data from 3 functionality tested, while validation testing produce 100% valid data from 111 tested functionalities. In compatibility testing it is proven that this system can run on two browsers, namely Mozilla Firefox and Internet Explorer.